Pestiviruses infection: Interferon-virus mutual regulation - Hong, Tianqi; Yang, Yi; Wang, Pengzhi; Zhu, Guoqiang; Zhu, Congrui (Frontiers in Cellular and Infection Microbiology, 2023)
Pestiviruses are a class of viruses that in some cases can cause persistent infection of the host, thus posing a threat to the livestock industry. Interferons (IFNs) are a group of secreted proteins that play a crucial role in antiviral defense. In this review, on the one hand, we elaborate on how pestiviruses are recognized by the host retinoic acid-inducible gene-I (RIG-I), melanoma-differentiation-associated protein 5 (MDA5), and Toll-like receptor 3 (TLR3) proteins to induce the synthesis of IFNs. On the other hand, we focus on reviewing how pestiviruses antagonize the production of IFNs utilizing various strategies mediated by self-encoded proteins, such as the structural envelope protein (Erns) and non-structural protein (Npro). Hence, the IFN signal transduction pathway induced by pestiviruses infection and the process of pestiviruses blockade on the production of IFNs intertwines into an intricate regulatory network. By reviewing the interaction between IFN and pestiviruses (based on studies on BVDV and CSFV), we expect to provide a theoretical basis and reference for a better understanding of the mechanisms of induction and evasion of the innate immune response during infection with these viruses.